Forage Moisture Testing - Carrol G. Chambliss (editor) (EDIS)
This document is SS-AGR-178, one of a series of the Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published 1999. Revised August 2002.